Macro Policy Lessons for a Sound Design of Fiscal Decentralization. (Policy Papers; Policy Paper ;, 2009)
Fiscal decentralization has been, and remains high on the policy agenda of many countries. It is mainly driven by political pressures, which tend to be especially evident in countries with multiple ethnicities, and/or wide regional disparities in incomes or resource endowments. More generally, decentralization pressures frequently reflect a desire for more participatory government and greater voice of local constituents in the allocation of budgetary resources. Regardless of its motivation, fiscal decentralization can have important macroeconomic implications. Therefore, Fund advice to member countries (whether in the context of surveillance, program design, or technical assistance) has often focused on the design and implementation of intergovernmental fiscal arrangements. This paper distills the main lessons from the Fund's engagement with member countries in this area, drawing in particular, (but not exclusively) on technical assistance (TA) provided by the Fiscal Affairs Department (FAD) to ten countries which are broadly representative of the range of members that have requested assistance in this area.